SISTEM PENDUKUNG KEPUTUSAN UNTUK TANAMAN HORTIKULTURA DENGAN METODE DESAIN SPRINT - Trismayanti Dwi Puspitasari; Nanik Anita (Jurnal Teknologi Informasi dan Terapan, 2019)
The selection of plants to be planted is not easy for people who are unfamiliar with knowledge of horticulture, so an application is needed to develop with a decision support system that can help decide which plants are planted according to the pH, temperature, rainfall and height of land. The development methodology that will be used is the sprint design. The design sprint is very suitable for projects that require fast time to get a solution because it is a shortcut that can be used before creating and launching a product, so that it can cut the required budget. The aim of this research are made prototype system that able to provide information about the types of plants using design sprint method.